Trovafloxacin, a new fluoroquinolone with potent activity against Streptococcus pneumoniae. - Thomson, K S (1997)
An in vitro study of the activity of 15 antibacterial agents against 202 recent pediatric isolates of Streptococcus pneumoniae from urban and rural Nebraska and rural Kentucky identified trovafloxacin, ofloxacin, clindamycin, and vancomycin as the most active agents and equally active against both penicillin-susceptible and--resistant strains. In contrast, six beta-lactams, three macrolides, and trimethoprim-sulfamethoxazole were less active overall, especially against penicillin-intermediate and--resistant strains. Trovafloxacin inhibited all strains at a concentration of < or = 0.25 micrograms/ml and was 8- to 16-fold more potent than ofloxacin or ciprofloxacin.